Ultrasound-Guided Percutaneous Drainage of Abdominal Abscess in a Patient With Crohn's Disease: A Case Report - Karpova, Radmila V.; Russkova, Ksenia S.; Komarov, Roman N.; Petrova, Arina A. (Frontiers in Surgery, 2021)
Introduction: The autoimmune process in Crohn's disease exacerbates destructive changes in the intestinal wall and leads to complications such as bleeding (21.9%), strictures (21.6%), and abscesses (19.7%). Case presentation: The case of a 32-year-old male patient with an 8-year history of Crohn’s disease is presented. He was admitted for emergency indications with severe pain in the right lower quadrant, chills, and a fever reaching 39.0 °C. The patient had anemia, hypocoagulation and immunodeficiency. Ultrasound and CT scans of the abdominal organs revealed an abscess in the right iliac region. It was immediately drained under ultrasound control and X-ray. A fistulogram showed the fistula between the abscess and the ileum. Routine antibiotic therapy selected in accordance with the sensitivity of the microflora and sanitization of the abscess cavity were not effective. The immunomodulatory therapy, intravenous administration of cryoprecipitate, and the introduction of fibrin glue into the abscess cavity were added to the treatment. After the treatment, the patient’s immune status corresponded to normal, the abscess healed, and the fistula was closed. Conclusion: In patients suffering from Crohn's disease with the formation of an abscess and a long-term non-healing intestinal fistula, it is essential that the diagnostic algorithm includes the examination of the immune status. Treatment should include immunomodulators, intravenous administration of cryoprecipitate. To close the fistula in these patients, it is advisable to use fibrin glue that has a local immunomodulatory effect.